(untitled) (Bangladesh Journal of Microbiology, 2020)
A highly cellulolytic bacterium was locally isolated from rice straw and identified as Stenotrophomonas maltophilia. Identification of the isolate based on the morphological, cultural and biochemical characteristics was confirmed with 16S rDNA analysis. The bacterium showed the highest level of reducing sugar and extracellular protein production when incubated for 3 days (348.75 μg/ml and 288.5 μg/ml respectively) at 40°C temperature (463.0 μg/ ml and 333.0 μg/ml respectively) and pH 6.5 (360.0 μg/ml and 349.0 μg/ml respectively) in Winstead’s broth having 1.5% CMC and 0.2% Yeast Extract as carbon and nitrogen source respectively. Crude cellulase enzymes produced by the bacterium showed the highest CMCase activity rather than FPase, Avicelase and ²-Glucosidase activities. Cellulase activity of the crude enzyme was also determined using the same parameters. The crude cellulase enzyme showed the highest CMCase activity when incubated for 60 minutes (232.5 U/ml), at pH 6.5 (105.0 U/ml), 35°C temperature (69.75 U/ml) using CMC and Peptone as carbon and nitrogen source respectively. Crude cellulase showed the highest activity in presence of mercury and SDS as metal and detergent respectively. Substrate specificity and SDS-PAGE analysis reveals that the cellulase may be an endo-1,4-glucanase. Bangladesh J Microbiol, Volume 37 Number 1 June 2020, pp 15-22